Arctic Birds, #11. CAFF Technical Report No. 21. - Soloviev, M.Y.; Tomkovich, P.S. (CAFF International Secretariat, 2010)
"The focus of this issue of the bulletin of the Arctic Birds Breeding Conditions Survey (ABBCS) is the reproductive performance of birds in relation to their environment in the Arctic and Subarctic in summer 2008. Arctic terrestrial ecosystems are remarkable for pronounced fluctuations in the abundance and/or productivity at their high trophic levels, in birds and mammals. These unstable systems could have been expected to show quick response to increasing temperatures and precipitation across most of the Arctic during the recent decades. However, so far, the results of observations on the impacts of climate change in terrestrial ecosystems are less alarming compared with the melting of sea- ice and impacts on marine animals (http://www.arctic. noaa.gov/reportcard). Apparently, this is partly due to a limited current understanding of the response of Arctic wildlife and ecosystems to both natural and human-induced changes. Several activities implemented in the framework of the International Polar Year 2007–2008 were aimed at filling this gap, for example Arctic Wildlife Observatories Linking Vulnerable EcoSystems (ArcticWOLVES). This project builds a network of circumpolar wildlife observatories in order to assess the current state of Arctic terrestrial food webs over a large geographical range (http://www.cen.ulaval.ca/arctic-wolves/index.html). This and similar initiatives made an important contribution to the geographic coverage by ABBCS in 2008, and we anticipate that coordinated monitoring in future will help to obtain a better picture of ecosystem processes developing at a pan-Arctic scale." /./